CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

A Submatrix-Based Method for Approximate Matrix Function Evaluation in the Quantum Chemistry Code CP2K - Lass, Michael; Schade, Robert; Kühne, Thomas; Plessl, Christian (Proc. International Conference for High Performance Computing, Networking, Storage and Analysis (SC))
Electronic structure calculations based on density-functional theory (DFT) represent a significant part of today's HPC workloads and pose high demands on high-performance computing resources. To perform these quantum-mechanical DFT calculations on complex large-scale systems, so-called linear scaling methods instead of conventional cubic scaling methods are required. In this work, we take up the idea of the submatrix method and apply it to the DFT computations in the software package CP2K. For that purpose, we transform the underlying numeric operations on distributed, large, sparse matrices into computations on local, much smaller and nearly dense matrices. This allows us to exploit the full floating-point performance of modern CPUs and to make use of dedicated accelerator hardware, where performance has been limited by memory bandwidth before. We demonstrate both functionality and performance of our implementation and show how it can be accelerated with GPUs and FPGAs.

Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.

Accessing the Accuracy of Density Functional Theory through Structure and Dynamics of the Water–Air Interface - Ohto, Tatsuhiko; Dodia, Mayank; Xu, Jianhang; Imoto, Sho; Tang, Fujie; Zysk, Frederik; Kühne, Thomas D.; Shigeta, Yasuteru; Bonn, Mischa; Wu, Xifan; Nagata, Yuki (The Journal of Physical Chemistry Letters)

Unconventional phase III of high-pressure solid hydrogen - Azadi, Sam; Kühne, Thomas D. (Physical Review B)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas D.; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)

Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Experimental and theoretical (high energy resolution) X-ray absorption and emission spectroscopy / vorgelegt von Patrick Müller ; [Promotionskommission: Prof. Dr.-Ing. Hans-Joachim Warnecke, Vorsitz; Prof. Dr. Matthias Bauer, Erstgutachter; Prof. Dr. Thomas D. Kühne, Zweitgutachter; Prof. Dr. Wolf Gero Schmidt] - Müller, Patrick

Properties of Co-Evaporated RbInSe2 Thin Films - Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Bertram, Tobias; Maticiuc, Natalia; Yetkin, Hasan A; Gunder, René; Schlatmann, Rutger; Kühne, Thomas D; Kaufmann, Christian A; Mirhosseini, Hossein (physica status solidi (RRL)--Rapid Research Letters)

Opposing Electronic and Nuclear Quantum Effects on Hydrogen Bonds in H2O and D2O - Clark, Timothy; Heske, Julian Joachim; Kühne, Thomas (ChemPhysChem)
Abstract The effect of extending the O−H bond length(s) in water on the hydrogen-bonding strength has been investigated using static ab initio molecular orbital calculations. The “polar flattening” effect that causes a slight σ-hole to form on hydrogen atoms is strengthened when the bond is stretched, so that the σ-hole becomes more positive and hydrogen bonding stronger. In opposition to this electronic effect, path-integral ab initio molecular-dynamics simulations show that the nuclear quantum effect weakens the hydrogen bond in the water dimer. Thus, static electronic effects strengthen the hydrogen bond in H2O relative to D2O, whereas nuclear quantum effects weaken it. These quantum fluctuations are stronger for the water dimer than in bulk water.
Keywords: ab initio calculations; bond theory; hydrogen bonds; isotope effects; solvent effects

Impact of intermolecular vibrational coupling effects on the sum-frequency generation spectra of the water/air interface - Kaliannan, Naveen Kumar; Henao Aristizabal, Andres; Wiebeler, Hendrik; Zysk, Frederik; Ohto, Tatsuhiko; Nagata, Yuki; D. Kühne, Thomas (Molecular Physics)

Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Controlling the strength of interaction between carbon dioxide and nitrogen-rich carbon materials by molecular design - Walczak, Ralf; Savateev, Aleksandr; Heske, Julian Joachim; Tarakina, Nadezda V.; Sahoo, Sudhir; Epping, Jan D.; Kühne, Thomas; Kurpil, Bogdan; Antonietti, Markus; Oschatz, Martin (Sustainable Energy Fuels)
Thermal treatment of hexaazatriphenylene-hexacarbonitrile (HAT-CN) in the temperature range from 500 °C to 700 °C leads to precise control over the degree of condensation{,} and thus atomic construction and porosity of the resulting C2N-type materials. Depending on the condensation temperature of HAT-CN{,} nitrogen contents of more than 30 at% can be reached. In general{,} these carbons show adsorption properties which are comparable to those known for zeolites but their pore size can be adjusted over a wider range. At condensation temperatures of 525 °C and below{,} the uptake of nitrogen gas remains negligible due to size exclusion{,} but the internal pores are large and polarizing enough that CO2 can still adsorb on part of the internal surface. This leads to surprisingly high CO2 adsorption capacities and isosteric heat of adsorption of up to 52 kJ mol−1. Theoretical calculations show that this high binding enthalpy arises from collective stabilization effects from the nitrogen atoms in the C2N layers surrounding the carbon atom in the CO2 molecule and from the electron acceptor properties of the carbon atoms from C2N which are in close proximity to the oxygen atoms in CO2. A true CO2 molecular sieving effect is achieved for the first time in such a metal-free organic material with zeolite-like properties{,} showing an IAST CO2/N2 selectivity of up to 121 at 298 K and a N2/CO2 ratio of 90/10 without notable changes in the CO2 adsorption properities over 80 cycles.

Enhancement of the asymmetry in the hydrogen bond network of liquid water by an ultrafast electric field pulse - Elgabarty, Hossam; Kaliannan, Naveen Kumar; Kühne, Thomas D. (Scientific Reports)

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas D.; Mirhosseini, Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

A General Algorithm to Calculate the Inverse Principal p-th Root of Symmetric Positive Definite Matrices - Richters, Dorothee; Lass, Michael; Walther, Andrea; Plessl, Christian; Kühne, Thomas (Communications in Computational Physics)
We address the general mathematical problem of computing the inverse p-th root of a given matrix in an efficient way. A new method to construct iteration functions that allow calculating arbitrary p-th roots and their inverses of symmetric positive definite matrices is presented. We show that the order of convergence is at least quadratic and that adaptively adjusting a parameter q always leads to an even faster convergence. In this way, a better performance than with previously known iteration schemes is achieved. The efficiency of the iterative functions is demonstrated for various matrices with different densities, condition numbers and spectral radii.

Using Approximate Computing for the Calculation of Inverse Matrix p-th Roots - Lass, Michael; Kühne, Thomas; Plessl, Christian (Embedded Systems Letters)
Approximate computing has shown to provide new ways to improve performance and power consumption of error-resilient applications. While many of these applications can be found in image processing, data classification or machine learning, we demonstrate its suitability to a problem from scientific computing. Utilizing the self-correcting behavior of iterative algorithms, we show that approximate computing can be applied to the calculation of inverse matrix p-th roots which are required in many applications in scientific computing. Results show great opportunities to reduce the computational effort and bandwidth required for the execution of the discussed algorithm, especially when targeting special accelerator hardware.

Theoretical Investigation of Interaction of CuInSe2 Absorber Material with Oxygen, Hydrogen, and Water - Sahoo, Sudhir; Kormath Madam Raghupathy, Ramya; Kühne, Thomas; Mirhosseini, Hossein (J. Phys. Chem. C)
We performed ab initio calculations to study oxygen and hydrogen point defects in the CuInSe2 (CISe) solar-cell material. We found that H interstitial defects (when one H atom is surrounded by four Se atoms) and HCu (when a H atom is replacing a Cu atom) are the most stable defects. Whereas these H substitutional defects remain neutral, H interstitial defects act as donor defects and are detrimental to the cell performance. The incorporation of H2 into the CISe lattice, on the other hand, is harmless to the p-type conductivity. Oxygen atoms tend to either substitute Se atoms in the CISe lattice or form interstitial defects, though the formation of substitutional defects is more favorable. All oxygen point defects have high formation energies, which results in a low concentration of these defects in CISe. However, the presence of oxygen in the system leads to the formation of secondary phases such as In2O3 and InCuO2. In addition to the point defects, we studied the adsorption of H2O molecules on a defect-free surface and a surface with a (2VCu + InCu) defect using the ab initio thermodynamics technique. Our results indicate that the dissociative water adsorption on the CISe surface is energetically unfavorable. Furthermore, in order to obtain a water-free surface, the surface with defects has to be calcined at a higher temperature compared to the defect-free surface.

Database screening of ternary chalcogenides for p-type transparent conductors - Kormath Madam Raghupathy, Ramya; Wiebeler, Hendrik; Kühne, Thomas; Felser, Claudia; Mirhosseini, Hossein (Chemistry of Materials)
In this work, we investigated ternary chalcogenide semiconductors to identify promising p-type transparent conducting materials (TCMs). High-throughput calculations were employed to find the compounds that satisfies our screening criteria. Our screening strategy was based on the size of band gaps, the values of hole effective masses, and p-type dopability. Our search led to the identification of seven promising compounds (IrSbS, Ba2GeSe4, Ba2SiSe4, Ba(BSe3)2, VCu3S4, NbCu3Se4, and CuBS2) as potential TCM candidates. In addition, branch point energy and optical absorption spectra calculations support our findings. Our results open a new direction for the design and development of p-type TCMs.

Impact of finite-temperature and condensed-phase effects on theoretical X-ray absorption spectra of transition metal complexes - Müller, Patrick; Karhan, Kristof; Krack, Matthias; Gerstmann, Uwe; Schmidt, Wolf Gero; Bauer, Matthias; Kühne, Thomas D. (Journal of Computational Chemistry)

A Massively Parallel Algorithm for the Approximate Calculation of Inverse p-th Roots of Large Sparse Matrices - Lass, Michael; Mohr, Stephan; Wiebeler, Hendrik; Kühne, Thomas; Plessl, Christian (Proc. Platform for Advanced Scientific Computing (PASC) Conference)
We present the submatrix method, a highly parallelizable method for the approximate calculation of inverse p-th roots of large sparse symmetric matrices which are required in different scientific applications. Following the idea of Approximate Computing, we allow imprecision in the final result in order to utilize the sparsity of the input matrix and to allow massively parallel execution. For an n x n matrix, the proposed algorithm allows to distribute the calculations over n nodes with only little communication overhead. The result matrix exhibits the same sparsity pattern as the input matrix, allowing for efficient reuse of allocated data structures. We evaluate the algorithm with respect to the error that it introduces into calculated results, as well as its performance and scalability. We demonstrate that the error is relatively limited for well-conditioned matrices and that results are still valuable for error-resilient applications like preconditioning even for ill-conditioned matrices. We discuss the execution time and scaling of the algorithm on a theoretical level and present a distributed implementation of the algorithm using MPI and OpenMP. We demonstrate the scalability of this implementation by running it on a high-performance compute cluster comprised of 1024 CPU cores, showing a speedup of 665x compared to single-threaded execution.
Keywords: approximate computing; linear algebra; matrix inversion; matrix p-th roots; numeric algorithm; parallel computing

Efficient PAW-based bond strength analysis for understanding the In/Si(111)(8 × 2) – (4 × 1) phase transition - Lücke, Andreas; Gerstmann, Uwe; Kühne, Thomas D.; Schmidt, Wolf G. (Journal of Computational Chemistry)
A numerically efficient yet highly accurate implementation of the crystal orbital Hamilton population (COHP) scheme for plane-wave calculations is presented. It is based on the projector-augmented wave (PAW) formalism in combination with norm-conserving pseudopotentials and allows to extract chemical interactions between atoms from band-structure calculations even for large and complex systems. The potential of the present COHP implementation is demonstrated by an in-depth analysis of the intensively investigated metal-insulator transition in atomic-scale indium wires self-assembled on the Si(111) surface. Thereby bond formation between In atoms of adjacent zigzag chains is found to be instrumental for the phase change. © 2017 Wiley Periodicals, Inc.
Keywords: density functional theory; bonding; crystal orbital Hamilton population; indium nanowires; phase transition

High-pressure hydrogen sulfide by diffusion quantum Monte Carlo - Azadi, Sam; Kühne, Thomas D. (The Journal of Chemical Physics)

Efficient PAW-based bond strength analysis for understanding the In/Si(111)(8 × 2) - (4 × 1) phase transition - Lücke, Andreas; Gerstmann, Uwe; Kühne, Thomas D.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

N-Heterocyclic Carbene Complexes of Iron as Photosensitizers for Light-Induced Water Reduction - Zimmer, Peter; Müller, Patrick; Burkhardt, Lukas; Schepper, Rahel; Neuba, Adam; Steube, Jakob; Dietrich, Fabian; Flörke, Ulrich; Mangold, Stefan; Gerhards, Markus; Bauer, Matthias (European Journal of Inorganic Chemistry)

Improved parameterization of the quantum harmonic oscillator model based on localized wannier functions to describe Van der Waals interactions in density functional theory - Partovi-Azar, Pouya; Berg, Matthias; Sanna, Simone; Kühne, Thomas D. (International Journal of Quantum Chemistry)
Recently, the quantum harmonic oscillator model has been combined with maximally localized Wannier functions to account for long-range dispersion interactions in density functional theory calculations (Silvestrelli, J. Chem. Phys. 2013, 139, 054106). Here, we present a new, improved set of values for the three parameters involved in this scheme. To test the new parameter set we have computed the potential energy curves for various systems, including an isolated Ar2 dimer, two N2 dimers interacting within different configurations, and a water molecule physisorbed on pristine graphene. While the original set of parameters generally overestimates the interaction energies and underestimates the equilibrium distances, the new parameterization substantially improves the agreement with experimental and theoretical reference values. © 2016 Wiley Periodicals, Inc.
Keywords: Wannier orbitals; Van der Waals interactions; density functional theory; quantum harmonic oscillator

Assessing the accuracy of improved force-matched water models derived from Ab initio molecular dynamics simulations - Köster, Andreas; Spura, Thomas; Rutkai, Gábor; Kessler, Jan; Wiebeler, Hendrik; Vrabec, Jadran; Kühne, Thomas D. (Journal of Computational Chemistry)
The accuracy of water models derived from ab initio molecular dynamics simulations by means on an improved force-matching scheme is assessed for various thermodynamic, transport, and structural properties. It is found that although the resulting force-matched water models are typically less accurate than fully empirical force fields in predicting thermodynamic properties, they are nevertheless much more accurate than generally appreciated in reproducing the structure of liquid water and in fact superseding most of the commonly used empirical water models. This development demonstrates the feasibility to routinely parametrize computationally efficient yet predictive potential energy functions based on accurate ab initio molecular dynamics simulations for a large variety of different systems. © 2016 Wiley Periodicals, Inc.
Keywords: liquid water; force matching; ab initio; molecular dynamics; Monte Carlo

Quantum ring-polymer contraction method: Including nuclear quantum effects at no additional computational cost in comparison to ab Initio molecular dynamics - John, Christopher; Spura, Thomas; Kühne, Thomas D. (Phys. Rev. E)

Using Approximate Computing in Scientific Codes - Lass, Michael; Kühne, Thomas; Plessl, Christian (Workshop on Approximate Computing (AC))

Covalency of hydrogen bonds in liquid water can be probed by proton nuclear magnetic resonance experiments - Elgabarty, Hossam; Khaliullin, Rustam Z.; Kühne, Thomas D. (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Sign problem of the fermionic shadow wave function - Calcavecchia, Francesco; Pederiva, Francesco; Kalos, Malvin H.; Kühne, Thomas D. (Phys. Rev. E)

Self-consistent field theory based molecular dynamics with linear system-size scaling - Richters, Dorothee (J. Chem. Phys.)

Electronic signature of the instantaneous asymmetry in the first coordination shell of liquid water - Kühne, Thomas D.; Khaliullin, Rustam Z. (Nature Commun.)